Placemaking as a vector and development instrument in the post-pandemic context - Emmendoerfer, Magnus Luiz; Vasconcelos, Caio Augusto de Souza; Mediotte, Elias José; Junior, Alessandro Carlos da Silva; Vitória, José Ricardo; Knupp, Marcos Eduardo Carvalho Gonçalves; Locatelli, Débora Regina Schneider; Barbosa, Mária de Fátima Nóbrega; Matos, Beatriz Gondim; Olavo, Antônio Vagner Almeida (Seven Editora, 2023)
The resumption of local development, in a post-pandemic scenario, is one of the great challenges for cities. In tourist cities, where tourism is an important economic pillar, initiatives for the regeneration and requalification of urban spaces as a promoter of social interactions, cooperation, and economic opportunities, enhance the adoption of Placemaking practices. Therefore, the objective of this essay is to present propositions and considerations for the application of Placemaking as a vector and instrument of local development in articulation with tourism, based on creativity and collaboration. As a result, it is observed that urban transformations under this guideline demand structural adjustments and require local reconfiguration, especially in a post-pandemic context. In this sense, it is observed that the aspects treated can help in carrying out diagnoses and formulating Creative Placemaking projects for local tourism development, linking actions to the entrepreneurial behavior of individuals and the Sustainable Development Goals of the United Nations Organization. DOI: https://doi.org/10.56238/devopinterscie-075